Revolutionizing Healthcare with 3D/4D Printing and Smart Materials - Isaac John Ibanga; Onibode Bamidele; Cyril B. Romero; Al-Rashiff Hamjilani Mastul; Yamta Solomon; Cristina Beltran Jayme (Engineering Science Letter, 2023)
3D printing technology has revolutionized the way products are manufactured, and it has opened up new possibilities in the field of smart materials. Smart materials are materials that can change their properties in response to external stimuli, such as temperature, pressure, or light. By combining 3D printing technology with smart materials, highly customizable and responsive products are created. The addition of the time dimension to 3D printing has introduced 4D printing technology, which has gained considerable attention in different fields such as medical, art, and engineering. To bridge the gap in knowledge of 4D, this paper assessed the revolution in healthcare with 3D/4D printing and smart materials. Data was generated as part of a broader empirical study which sought to explore healthcare personnel and electrical engineers’ perception on the practices around the use of 3D/4D printing technology and smart materials. The main method used was structured interviews. 12 participant were purposively selected and interviewed including healthcare personnel and electrical engineers form Philippines and Nigeria. The findings reveal an array of activities undertaken using both 3D and 4D. Furthermore, the study revealed that 4D printing is a new generation of 3D printing. Another aspect of the 3D usage is the integration of electrical stimulation and smart implant as a new area of study in healthcare. 3D could also be used to monitoring the smart implant performance. The study also evaluate the possibility of using Internet of things (IoT) in the smart implant as some device embeds smart materials. Smart implant commonly used includes orthopedic applications, such as knee and hip replacement, spine fusion, and fracture fixation. The smart materials used in this technology are important because 3D printing allows printed structures to be dynamic. The paper highpoints is that 4D printing has great potential for the future.